Una mirada cuantitativa a la situación de pobreza de los hogares indígenas en el Perú - Trivelli, Carolina (2005)
This document is based on the reading of collected by the surveys with the objective to relate the variables of poverty and ethnicity for the Peruvian case. One of its main results is that Peru is a country with an important indigenous population. Altogether the 33.7% of the Peruvian homes are indigenous homes, being the main ethnic group the one of Quechua speech (77% of the indigenous homes). These homes face indices of superior poverty mainly and extreme poverty that the non-indigenous homes: of the total of poor homes the 43.4% are indigenous, whereas the 52.4% of extreme the poor homes are indigenous. The obtained results show that although the being member of an indigenous home is related to the condition of poverty (the probability of being poor is greater 11% in the indigenous homes that in the non-indigenous homes), this relation varies from a region to another one, being narrower in area rural and nonexistent means in Metropolitan Lima. Also, along with the education, the experience and the region, the indigenous condition is excellent in the determination of the labor income, since the members of non-indigenous homes have labor income that practically double the income of the members of indigenous homes. But, the ethnic variable is not single in the characterization of the differences in the Peruvian homes, because in all the subjects treated in this document they appear two additional variables that are necessary to understand the differences: geographic location and gender.